Tidal Datum Changes Induced by Morphological Changes of North Carolina Coastal Inlets - Jindong Wang; Edward Myers (Journal of Marine Science and Engineering, 2016)
In support of the National Oceanic and Atmospheric Administration’s VDatum program, a new version of a tidal datum product for the North Carolina coastal waters has been developed to replace the initial version released in 2004. Compared with the initial version, the new version used a higher resolution grid to cover more areas and incorporated up-to-date tide, bathymetry, and shoreline data. Particularly, the old bathymetry datasets that were collected from the 1930s to the 1970s and were used in the initial version have been replaced by the new bathymetry datasets collected in the 2010s in the new version around five North Carolina inlets. This study aims at evaluating and quantifying tidal datum changes induced by morphological changes over about 40 to 80 years around the inlets. A series of tidal simulations with either the old or new bathymetry datasets used around five inlets were conducted to quantify the consequent tidal datum changes. The results showed that around certain inlets, approximately 10% change in the averaged depth could result in over 30% change in the tidal datum magnitude. Further investigation also revealed that tidal datum changes behind the barrier islands are closely associated with the cross-inlet tidal flux changes.